Increased susceptibility to streptozotocin and impeded regeneration capacity of beta‐cells in adult offspring of malnourished rats. (17th June 2013) - Goosse, K.; Bouckenooghe, T.; Sisino, G.; Aurientis, S.; Remacle, C.; Reusens, B.
Abstract Background Epidemiological studies related poor maternal nutrition and subsequent growth retardation in the progeny to the development of diabetes later in life. Low‐protein diet during gestation altered the beta‐cell development of the rat progeny by decreasing beta‐cell proliferation and increasing their sensitivity to nitric oxide and cytokines in the foetus. This disturbed maternal environment had long‐lasting consequences because the higher beta‐cell vulnerability was maintained at adulthood. Aim The aim of this study was to determine whether early malnutrition influences the vulnerability and the regeneration capacity of beta‐cells after streptozotocin (STZ) damage at adulthood. Methods Gestating rats were fed either a control or a low‐protein diet until weaning. Adult female offspring received injections of Freund's adjuvant weekly for 5 weeks followed 24 h later by STZ. Half of the cohort was killed at d34, whereas the other half was maintained until d48 to analyse the regeneration capacity of the beta‐cells. Results Although control and low‐protein rats had equivalent pancreatic insulin content and beta‐cell volume density at d34, hyperglycaemia appeared earlier and was more dramatic in low‐protein rats than in control rats. STZ treatment increased beta‐cell proliferation similarly in both groups. At d48, apoptotic rate was higher in the low‐protein group. Regeneration appeared in control, but not in the low‐protein rats, where beta‐cell aggregates/surface area and Reg1‐positive area were decreased compared to control. Conclusion Maternal malnutrition programmes a more vulnerable endocrine pancreas in the progeny which is unable to regenerate after injury, therefore predisposing it to develop glucose intolerance and diabetes later in life.